He started it [large type] - Downing, Samantha (Thorndike Press, a part of Gale, a Cengage Company, 2020)
"Beth, Portia, and Eddie Morgan haven't all been together in years. And for very good reasons--we'll get to those later. But when their wealthy grandfather dies and leaves a cryptic final message in his wake, the siblings and their respective partners must come together for a cross-country road trip to fulfill his final wish and--more importantly--secure their inheritance. But time with your family can be tough. It is for everyone. It's even harder when you're all keeping secrets and trying to forget a memory--a missing person, an act of revenge, the man in the black truck who won't stop following your car--and especially when at least one of you is a killer and there's a body in the trunk. Just to name a few reasons. But money is a powerful motivator. It is for everyone"--!cProvided by publisher.